The impact of bisphenol an exposure in utero and postnatal trans-fat diet on small intestine global DNA methylation and gut microbiome of sprague dawley rats / Sarah Zulkifli - Zulkifli, Sarah (2023)
A multitude of evidence has pointed out the repercussions of prenatal bisphenol A (BPA) exposure with a postnatal high fat diet on offspring’s health. However, the information on how the interaction between these two variables affects the small intestinal cells and the gut microbiome is rather limited. Hence, we investigated the impact of postnatal trans fat diet (TFD) on the small intestinal morphology and global DNA methylation, as well as the gut microbiome of offspring exposed and non-exposed to prenatal BPA. Eighteen pregnant rats were administered with either unspiked control (CTL), vehicle control (P80) or BPA drinking water throughout pregnancy. Twelve weaned pups from each pregnancy group were given either normal diet (ND) or TFD from the postnatal week (PNW) 3 till PNW14; divided into CTLND, CTLTFD, P80ND, P80TFD, BPAND, and BPATFD groups. Body weight (BW), waist circumference (WC), food and water intake were measured weekly in offspring. At PNW14, small intestines were collected for global DNA methylation and histological analyses.